2017
DOI: 10.1177/1010428317694551
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and potential prognostic value of SMAD protein expression in chronic lymphocytic leukemia

Abstract: The SMAD proteins are responsible for transducing signals from activated transforming growth factor-beta. This is the first study assessing the expression of SMAD-1/8, SMAD-2/3, SMAD-4, and SMAD-7 in chronic lymphocytic leukemia cells with regard to their clinical significance and potential prognostic value. Overexpression of SMAD-1/8 was observed in 160 chronic lymphocytic leukemia patients compared to 42 healthy volunteers (p = 0.023) and was associated with a more progressive course of the disease (p = 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Altogether, our results suggest the existence of a TGF-β inactivation in primary CLL cells of progressive U-cases compared to stable patients. Although our data are not direct evidence of the cause of disease progression, they are in agreement with previous reports linking impairment of TGF-β pathway with poor clinical outcome in CLL [ 27 , 28 , 29 , 30 ]. In addition, these works propose that TGFβ-1 induces growth arrest in CLL cells, but about one-third of the patients are resistant to its effects [ 26 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Altogether, our results suggest the existence of a TGF-β inactivation in primary CLL cells of progressive U-cases compared to stable patients. Although our data are not direct evidence of the cause of disease progression, they are in agreement with previous reports linking impairment of TGF-β pathway with poor clinical outcome in CLL [ 27 , 28 , 29 , 30 ]. In addition, these works propose that TGFβ-1 induces growth arrest in CLL cells, but about one-third of the patients are resistant to its effects [ 26 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…TGF-β protein is a pleiotropic cytokine and exerts its effect on gene expression through transcription factors known as SMAD proteins. Specifically, in CLL, different works support the role of TGF-β pathway as a growth inhibitor of CLL cells [ 40 ], and recently, SMAD protein expression has been correlated with disease progression [ 29 ]. In view of these data and our previous results, we evaluated the activation of the TGF-β axis in stable and progressive U-CLLs by comparing mRNA levels of SMAD-2, SMAD-3, SMAD-4, and SMAD-7 as well as of two recognized target genes of the TGF-β pathway, cyclin-dependent kinase inhibitor 1A (p21 −Cip1 ) [ 41 ] and KLF10 (Kruppel Like Factor 10) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, analysis of gene expression of the BMP signaling pathway in a cohort of 160 CLL patient samples showed alterations of SMAD1/8 that appeared overexpressed and correlated with a decrease in SMAD4 expression compared with control samples. High levels of SMAD1/8 transcripts expression were associated with poor prognosis [81]. Interestingly, gene expression analysis of two independent datasets showed that the levels of inhibitory Smads varied across different B-cell lymphomas [79].…”
Section: Bmp Pathway and Lymphoid Malignanciesmentioning
confidence: 99%